Article Review: Evaluation of the Biological Role and Gene Expression of CD144 in Colorectal Cancer - K. Majeed, Adian (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Colorectal cancer (CRC) remains a leading cause of cancer-related deaths worldwide, with tumor angiogenesis playing a pivotal role in its progression and metastasis. CD144 (VE-cadherin), a calcium-dependent adhesion molecule, is critical for endothelial cell integrity and has been linked to tumor angiogenesis and cancer stem cell phenotypes. This study aimed to evaluate the immunohistochemical expression of CD144 in benign colorectal lesions, normal adjacent tumor tissue (NRAT), and tumor tissues to elucidate its role in colorectal cancer progression. Multiple techniques, including immunohistochemistry, flow cytometry, Western blot, and qPCR, were used to assess CD144 expression and its association with the VEGF/VEGFR2 signaling pathway. Our results revealed no expression of CD144 in benign colorectal tissues, while adjacent normal tissues showed positive expression of CD144, suggesting tumor-induced endothelial activation. CD144 expression was absent in cancer tissues, supporting the hypothesis that stromal factors may regulate CD144 expression in the tumor-peripheral environment. The results highlight CD144 as a potential prognostic indicator of malignant transformation and tumor recurrence, as well as a potential marker of cancer stem cells in colorectal cancer. Understanding the mechanisms that regulate CD144 expression may provide novel therapeutic targets for inhibiting angiogenesis and tumor progression.